Current trends in digitalization for the improvement of logistics processes of manufacturing companies in Latin America - Joaquín Cortez Chávez, Gonzalo (2024)
Currently, digitalization hold an essential role in improving international trade operations, especially in logistics processes in companies into the manufacturing sector.This research is developed to analyze the current digitization trends for the improvement of the logistics processes of manufacturing companies in Latin America in the period 2019-2022.Likewise, it seeks to analyze these trends that benefit the sustainability and collaborative integration of the supply chain and determine their contribution to the quality and the innovation processes.The methodology applied is a narrative type, because it consists of reviewing articles and making use of bibliographic references from published research by various authors related to the subject.The main databases consulted were Scopus, Web of Science and Scielo.The results support that Industry 4.0 and the Internet of Things (IoT) point out digitization and automation of processes, since they merge information technology with production and logistics.The analysis of the current trends of these technological tools in logistics processes in companies into the manufacturing sector allows this investigation to serve as a basis for future researchs in this area.